2018
DOI: 10.1038/labinvest.2017.120
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase 4 promotes cisplatin-induced acute kidney injury via ROS-mediated programmed cell death and inflammation

Abstract: The goal of this study was to elucidate the functional role of Nox4 during acute kidney injury (AKI). NADPH oxidases are a major source of reactive oxygen species (ROS) in the kidney in normal and pathological conditions. Among NADPH oxidase isoforms, NADPH oxidase4 (Nox4) is highly expressed in the kidney and has an important role in kidney diseases, such as diabetic nephropathy and renal carcinoma. We previously found that Nox4 expression significantly increased in the toxic AKI model. However, its functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
121
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(124 citation statements)
references
References 36 publications
3
121
0
Order By: Relevance
“…PPBICA not only limited programmed cell death induced by TNF-α and TNF-α plus z-VAD, but also prevented cisplatin-induced necroptosis and apoptosis. Our previous study showed that cisplatin induced the activation of caspase3-dependent apoptosis and RIPK-mediated necroptosis of tubular epithelial cells [2,21,22]. This may lead to loss of tubular epithelial cells and tubule integrity, where adherent junctions are further damaged, back-leaking of tubular fluid and inflammatory responses accelerated, which causes renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…PPBICA not only limited programmed cell death induced by TNF-α and TNF-α plus z-VAD, but also prevented cisplatin-induced necroptosis and apoptosis. Our previous study showed that cisplatin induced the activation of caspase3-dependent apoptosis and RIPK-mediated necroptosis of tubular epithelial cells [2,21,22]. This may lead to loss of tubular epithelial cells and tubule integrity, where adherent junctions are further damaged, back-leaking of tubular fluid and inflammatory responses accelerated, which causes renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…11 Addi-tionally, NADPH oxidase 4 (NOX4) is a ROS-generating enzyme that participates in inflammatory processes, mainly through the NOX4/ROS pathway. 12,13 In human skin keratinocytes and mouse skin, the production of inflammatory cytokines increases via the NOX4/ROS signaling pathway. 12 Moreover, NOX4 aggravates nephrotoxicity by activating ROS-mediated programmed cell death.…”
mentioning
confidence: 99%
“…12 Moreover, NOX4 aggravates nephrotoxicity by activating ROS-mediated programmed cell death. 13 Thus, we hypothesized that NOX4 might regulate NLRP3-dependent pyroptosis via the ROS/ TXNIP axis and, therefore, we aimed to further investigate the mechanism of the role of NOX4 in DR.…”
mentioning
confidence: 99%
“…We also evaluated the expression of genes regulated by Hifs including mitochondrial Bnip3, glycolytic Gapdh, and reactive oxygen species (ROS) associated Nox4. Previously, it was shown that Nox4 in particular promotes cisplatin-induced AKI through increased ROS [41]. Further, ROS-mediated stress in general has been implicated in the severity of cisplatininduced kidney injury.…”
Section: Discussionmentioning
confidence: 99%